Family Burden in The Patients of Alcohol Dependence Syndrome Attending the Psychiatry Department of Tertiary Hospital - Subedi, Bibek; Singh , Pradipman (Journal of College of Medical Sciences-Nepal, 2025)
Background Substance abuse/dependence causes significant harm to self, family and society as a whole. The study of family burden in alcohol dependence assumes importance because the profile of the associated factors can both influence the outcome of the problem, and be useful in designing and planning interventions to help the families cope with alcohol dependence. The aim of the study measures the various aspects of burden on caregiver or family members of alcohol dependent patients. Methods A descriptive, cross-sectional, hospital-based study at Nepal Medical College and Teaching Hospital on 105 respondents (n=105) for 1 year (3rd October 2016 - 3rd September 2017) was carried at Attarkhel. Proforma, Family burden interview schedule (FBIS, Pai and Kapur1981) and Diagnostic Criteria for Research by the Division of Mental Health of the World Health Organization (WHO, 1992) as per Tenth Revision of International Classification of Diseases were tools used for data collection and the data was entered in MS-Excel and analyses was done by SPSS version 16. Results The subjective burden analysed found that spouse (59%) had more burden than non-spouse among caregivers. The burden was moderate among the female spouse and high among illiterate and unemployed ones. Conclusions This research suggests that there is moderate burden among the PCTs of the respondents and mainly spouse are the ones to be affected more. The increasing trend of alcohol consumption among males and females either literate or illiterate, employed or unemployed has a devastating role to the family as well as society.